Stable inheritance of Sinorhizobium meliloti cell growth polarity requires an FtsN-like protein and an amidase - Elizaveta Krol (Nature Portfolio, 2021)
In Sinorhizobium bacteria, cell elongation takes place only at new cell poles, generated by cell division. Here, Krol et al. show that an FtsN-like protein and a peptidoglycan amidase are crucial for reliable selection of the new cell pole as cell elongation zone.